'Everything is relative': Comparison processes in social judgment The 2002 Jaspars Lecture - Mussweiler, Thomas (European journal of social psychology, 2003)
Any judgment involves a comparison of the evaluated target to a pertinent norm or standard, so that comparison processes lie at the core of human judgment. Despite this prominent role, however, little is known about the psychological mechanisms that underlie comparisons and produce their variable consequences. To understand these consequences, one has to examine what target knowledge is sought and activated during the comparison process. Two alternative comparison mechanisms are distinguished. Similarity testing involves a selective search for evidence indicating that the target is similar to the standard and leads to assimilation. Dissimilarity testing involves a selective search for evidence indicating that the target is dissimilar from the standard and leads to contrast. Distinguishing between these alternative mechanisms provides an integrative perspective on comparison consequences in the realm of social comparison and beyond. Copyright © 2003 John Wiley & Sons, Ltd.